Superior Noise Suppression, Response Time, and Device Stability of Non‐Fullerene System over Fullerene Counterpart in Organic Photodiode. (11th August 2020) - Jang, Woongsik; Rasool, Shafket; Kim, Byung Gi; Kim, Jehan; Yoon, Jinhwan; Manzhos, Sergei; Lee, Hang Ken; Jeon, Il; Wang, Dong Hwan
Abstract: Herein, non‐fullerene acceptor‐based organic photodiodes are compared with fullerene acceptor‐based organic photodiodes. The non‐fullerene acceptor, ethylhexyl‐rhodanine‐benzothiadiazole‐coupled indacenodithiophene ( eh ‐IDTBR)‐based organic photodiodes show a higher detectivity (1.61 × 10 13  cm Hz 1/2 W −1 ) and a faster response time (≈ 2.7 µs) than the fullerene acceptor, [6, 6]‐phenyl C71 butyric acid methyl ester (PC71 BM)‐based organic photodiodes (3.25 × 10 12  cm Hz 1/2 W −1 and ≈ 6.24 µs, respectively) owing to the excellent dark current suppression of the carrier injection and the low trap density of eh ‐IDTBR. Moreover, the eh ‐IDTBR‐based photodetector shows better operational device stability than the fullerene counterpart under electrical and thermal stress. This is corroborated by the morphology and crystallography analyses, both of which reveal that the eh ‐IDTBR‐containing photo‐sensitive films remain intact after imposing an external stress. This study elucidates important key advantages of the non‐fullerene acceptor, eh ‐IDTBR, and sets a milestone as it compares the non‐fullerene acceptors and fullerene acceptors in organic photodiodes for the first time. This work sets a new record for the performance and stability of solution‐processable non‐fullerene acceptor‐based organic photodiodes. Abstract : A non‐fullerene‐acceptor is compared with a fullerene acceptor in organic photodiodes. The eh‐IDTBR‐based devices show 495% higher specific detectivity than the fullerene‐based devices. A response time comparable to that of the silicon photodiode is achieved from the non‐fullerene acceptor‐based devices. The non‐fullerene acceptor‐based devices demonstrate exceptional stability, withstanding external electrical and thermal stress during device operation.